Reproductive development of Lotus tenuis (fabaceae) crop defoliated at different times and intensities - Vignolio, Osvaldo; Cambareri, Gustavo Sebastián; Petigrosso, Lucas R; Murillo, Natalia Lorena; Maceira, Nestor Oscar (Scientific Research Publishing, 2019)
Lotus tenuis forage yield has been quantified under defoliation conditions in pastures, grasslands and under dual-purpose production of both livestock forage and seeds. However, little is known about the effects of defoliation management on L. tenuis flower and pod production and subsequent seed yield. Two field experiments were conducted to study the response of L. tenuis to defoliation at different flowering stages and intensities. In Experiment 1, crops were defoliated at the beginning of the flowering (DBF), mid-flowering (DMF) or full flowering (DFF). In Experiment 2, defoliation was in vegetative stage at low (LDI) or high (HDI) intensities. Defoliation in Experiment 1 neither affected plant cover nor the photosynthetically active radiation intercepted by the crop during pod production. There were less umbels with dehiscent (shattered) pods in the DFF treatment than in Control, DBF and DMF treatments. Flower peak occurred first in the Control, DBF and DMF treatments, and eight days later in DFF plots, however, seed yield was not affected (1324 ± 32.8 kg·ha-1). Defoliation intensity did not affect seed yield (962 ± 25.9 kg·ha-1) because of self-compensation which increased harvest index in HDI (14.5% ± 0.6%) compared to the Control and LDI (12.0% ± 0.3%) treatments. Plant survival was not affected by defoliation treatments in any of the experiments. Flowering can be synchronized through defoliation. The blooming of large numbers of flowers in a short time was achieved, reducing the number of shattered pods. Compensatory responses through plant plasticity conferred L. tenuis the ability to overcome defoliation without affecting seed yield. Lotus tenuis defoliation as management tool will be considered in future researches because it is possible to harvest forage and to increase seed yield through a reduction of shattered pods.